Efforts Teachers Islamic Religious Education in Developing Communication Ethics of Junior High School Students - Rahim, Abdul; Khatimah, Nurul; Arman, Arman (Lembaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2024)
The purpose of this study was to determine the efforts of Teacher Islamic Religious Education developing students' communication ethics. Descriptive qualitative was used in this study in an object, a particular set of conditions, a particular information collection system, or a particular group of people at a particular time. The sample of the study that all seventh grade students amounted to 24 people from 22 students and 2 Teacher Islamic Religious Education. The data collection techniques are 1) Observations, namely making direct observations; 2) This interview was conducted to support the results of observations, 3) Documentation related to the problem under study. The techniques of data analysis used are as follows: Inductive method, deductive method, and comparative method. The results showed that 1) Students' communication ethics, students' communication ethics are still very lacking, where students still use impolite language to their teachers when speaking; 2) Efforts that can be taken for a teacher are 1) giving motivation, 2) providing guidance. 3) Habituation of students to follow good things; 3) Supporting factors from obstacles in the development of communication ethics are supporting factors, namely: Family environment, and institutional environment. This is to further add insight to the understanding of communication ethics.